KEANEKARAGAMAN LALAT (Cyclorrapha: Diptera) PADA LOKASI PENJUALAN IKAN SEGAR DI KOTA PADANG - Putri, Pipi Yuliana; Jasmi, Jasmi; Zeswita, Armein Lusi (STKIP PGRI Sumbar, 2013)
ABSTRACTFly is kind on insect that include subordo Cyclorrapha, ordo Diptera is often we found in our activities and kind of surroundings. It bring microorganisme, virus, bactery, protozoa, and egg of worm. It is usually lived in a wet and damp place. Based on the researched about kind of fly (Cyclorrapha: Diptera) in location of fresh-fish sell in Padang City. This research have purposes to knowing kind of fly (Cyclorrapha: Diptera) in location of fresh-fish sell in Padang City. It is do in june-august 2013. It is survey of research and description analysis with identify at laboratorium. Taken sample is doing at three place such as: Pasar Raya, Pasar Bandar Buat dan Pasar Lubuk Buaya, and identification at laboratorium Taksonomi animal Biology FMIPA Universitas Andalas. From the final of research about kind of fly (Cyclorrapha: Diptera) in location of fresh-fish sell in Padang City can found five species of fly that include in three family and one subordo. Species of fly that found is Musca domestica, Chrysomya megacephala, Lucillia sp., Calliphora sp., Sarcophaga sp., and species that dominat is Musca domestica.